"I Live in Constant Fear of Highs, " the Daily Impact of Type 1 Diabetes. (December 2020) - Hughes, Allyson S; Bispham, Jeoffrey; Fan, Ludi; Nieves-Perez, Magaly; McAuliffe-Fogarty, Alicia H
Limited research exists regarding the burdens associated with type 1 diabetes (T1D). The study's objective was to understand the impact of T1D from people with T1D and caregivers of minors with T1D. Six focus groups were conducted, with a total of 31 participants. Participants included people with T1D, ages 23 to 72 (n = 17) and caregivers ages 34 to 55 (n = 14). Participants were recruited from T1D Exchange Glu. People with T1D reported time spent managing diabetes had greatest impact, while caregivers reported financial and employment sacrifices as most impactful. Our findings provide insight into the real-world daily impact of diabetes.